Classification and origin of pore–throat systems in tight sandstone reservoirs: a case study of the Xujiahe Formation in the Northeastern Sichuan Basin, China - Wang, Youzhi; Wang, Xiandong; Chen, Xuqiang; Li, Xiaohui; Wu, Jingfeng; Gao, Xiang; Peng, Jianliang; Wang, Biao; Xie, Yingyi; Wu, Haiguang (Frontiers in Earth Science, 2025)
IntroductionThe reservoirs of the Xujiahe Formation in the northeastern Sichuan Basin have complex rock components, strong pore–throat inhomogeneity, and large differences in the production capacity between wells, and the mechanism of high-quality pore–throat development must be clarified to support well deployment.MethodsTaking the tight sandstone reservoirs of the Xu-2 member of the Xujiahe Formation as the research object, this study establishes a pore–throat system classification, reveals the origins of various pore–throat systems, and conducts a microscopic analysis of the pore structure through thin sections, mercury intrusion capillary pressures, and nuclear magnetic resonance studies.ConclusionThe results show that four main types of reservoir spaces can be found in the cast thin section, namely primary InterP pores, residual InterP pores, dissolution pores, and IntraP pores. By observing the cast thin section, the pore–throat system can be classified into three categories: InterP pore–throat systems, mixed InterP-dissolutional pore–throat systems, and dissolution-IntraP pore–throat systems. The pore–throat systems of the reservoir are controlled by both the sedimentary environment and diagenesis, strong hydrodynamics, high quartz grain contents, low mud and calcareous clast contents, and moderate amounts of volcanic clasts that are favorable for chlorite film formation. A large number of intergranular pores are efficiently maintained, forming an intergranular pore–throat system with the best storage conditions. The research results can guide the study of the formation mechanism of the tight reservoirs in this area and also provide some reference for the evaluation of reservoir consistency.